Greatly Reduced Processing Temperature for a Solution‐Processed NiOx Buffer Layer in Polymer Solar Cells. Issue 12 (6th August 2013) - Zhai, Zhichun; Huang, Xiaodong; Xu, Meifeng; Yuan, Jianyu; Peng, Jun; Ma, Wanli
<x xml:space="preserve">Abstract</x> By application of thermal annealing and UV ozone simultaneously, a solution‐processed NiOx film can achieve a work function of approximately –5.1 eV at a temperature below 150 °C, which allows the processing of NiOx that is compatible with fabrication of polymer solar cells (PSCs) on plastic substrates. The low processing temperature, which is greatly reduced from 250–400 °C to 150 °C, is attributed to the high concentration of NiOOH species on the film surface. This concentration will result in a large surface dipole and lead to increased work function. The pretreated NiOx is demonstrated to be an efficient buffer layer in PSCs based on polymers with different highest occupied molecular orbital energy levels. Compared with conventional poly(3, 4‐ethylenedioxy‐thiophene):poly(styrenesulfonate)‐buffered PSCs, the NiOx‐buffered PSCs achieve similar or improved device performance as well as enhanced device stability.